2018
DOI: 10.1002/jhet.3218
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of Polyfluoroalkyl Substituted 6,7‐Dihydrobenzisoxazolones

Abstract: To a stirred solution of 2-(2-halogeno-2,2-difluoroacetyl) cyclohexane-1,3-diones (2a,b,f,g) (1.0 mmol) in dry chloroform (20 mL), oxalyl chloride (0.635 g, 3.0 mmol) and one drop of dimethylformamide were added. After stirring at room temperature for 2 h, chloroform and residual oxalyl chloride were evaporated in vacuo. The crude residue was purified by silica gel column chromatography to give the title compounds 4a,b,f,g in 75-78% yield.2-(2-Bromo-2,2-difluoroacetyl)-3-chlorocyclohex-2-en-1-one (4a). This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Khlebnicova et al reported regioselective synthesis of hitherto unreported 6,7-dihydro-1,2-benzisoxazol-4(5H)-ones 260 and 6,7-dihydro-2,1-benzisoxazol-4(5H)-ones 263 with 2polyfluoroalkanoylcyclohexane-1,3-diones 80 in good yields (Scheme 87). [170] Condensation between 80 and hydroxylamine hydrochloride 55 afforded 260 whereas regioisomeric products 263 could be obtained by the transformation of 80 into their vinylogous chlorides 261, the subsequent addition of sodium azide 262 in dimethylformamide involving the in situ formation of azides.…”
Section: Isoxazole Derivativesmentioning
confidence: 99%
“…Khlebnicova et al reported regioselective synthesis of hitherto unreported 6,7-dihydro-1,2-benzisoxazol-4(5H)-ones 260 and 6,7-dihydro-2,1-benzisoxazol-4(5H)-ones 263 with 2polyfluoroalkanoylcyclohexane-1,3-diones 80 in good yields (Scheme 87). [170] Condensation between 80 and hydroxylamine hydrochloride 55 afforded 260 whereas regioisomeric products 263 could be obtained by the transformation of 80 into their vinylogous chlorides 261, the subsequent addition of sodium azide 262 in dimethylformamide involving the in situ formation of azides.…”
Section: Isoxazole Derivativesmentioning
confidence: 99%
“…6,7-Dihydrobenzo[d]isoxazol-4(5H)-ones (Figure 1) are a class of compounds that can be prepared by 1,3-dipolar cycloaddition of nitrile oxides to cyclohexane-1,3-diones [3b] or condensation of 2-acylcycloxane-1,3-diones with hydroxylamine. [4] This scaffold contains two positions (3 and 6) into which a wide range of substituents can be introduced in the synthesis process and three positions (4, 5, and 7) by which the molecule can be further modified.…”
Section: Introductionmentioning
confidence: 99%
“…Analogs of benzisoxazole with different saturation degrees of the six‐membered cycle also found application for the synthesis of different biologically active substances, [3] but they are much less common in the literature. 6,7‐Dihydrobenzo[ d ]isoxazol‐4(5 H )‐ones (Figure 1) are a class of compounds that can be prepared by 1,3‐dipolar cycloaddition of nitrile oxides to cyclohexane‐1,3‐diones [3b] or condensation of 2‐acylcycloxane‐1,3‐diones with hydroxylamine [4] . This scaffold contains two positions (3 and 6) into which a wide range of substituents can be introduced in the synthesis process and three positions (4, 5, and 7) by which the molecule can be further modified.…”
Section: Introductionmentioning
confidence: 99%